Management of the irradiated N0-neck during salvage pharyngo-laryngeal surgery. Issue 6 (June 2020) - Mazerolle, Paul; Gorphe, Philippe; Vairel, Benjamin; Dupret-Bories, Agnès; Temam, Stéphane; Chaltiel, Léonor; Vergez, Sébastien
Abstract: Background: Salvage surgeries are challenging procedures, with an associated poor prognosis. Management of the N0 neck in those situations remains controversial. We aim to compare oncologic outcomes regarding neck management after surgery for N0 pharyngo-laryngeal carcinoma occurring after loco-regional radiotherapy. Methods: We conducted a multicentric retrospective study, including all patients undergoing surgery for persistent, recurrent or new primary N0 carcinoma of the oropharynx, hypopharynx or larynx between 2005 and 2015, following loco-regional radiotherapy. Results: A total of 239 patients were included, concerning respectively 44%, 34% and 22% oropharyngeal, laryngeal and hypopharyngeal tumors operated. A neck dissection was performed in 143 patients (60%), with an occult nodal metastasis rate of 9%. This rate was higher for hypopharyngeal carcinomas (18%, p = 0.16) and tumors with initial nodal involvement (16%, p = 0.05). With a median follow-up of 60 months, the median overall survival (OS) and progression-free survival rates (PFS) were 34 months and 25 months. We identified negative margin excision status, age at the time of surgery (under 60) and delay between RT and surgery over 2 years as the only variables associated with better OS (p < 0.0001 and p = 0.004) and PFS (p < 0.0001 and p = 0.010) in multivariable analysis, with no difference regarding neck management. Regional progression (alone or with distant metastasis) was noted in 10 cases: 4 in the neck observation group (4%) versus 6 in the neck dissection group (4%). Conclusion: Elective lymph node dissection of irradiated neck should not be routinely performed in patients undergoing surgery for persistent, recurrent or new primary pharyngo-laryngeal carcinomas